(untitled) (Dhaka University Journal of Science, 2015)
The recovery of a cationic dye, methylene blue (MB), from the residue generated during its removal via adsorption on starch-based adsorbents from aqueous solution was studied. Adsorption characteristics of MB on wheat flour (WF) and pure starch were analyzed using UV-visible spectroscopy. WF and starch were loaded with an optimum amount of MB producing MB-WF and MB-starch, respectively, leaving residues. The desorption characteristics and % recovery of MB from both the synthetic wastes were determined. The effects of yeast and temperature on the recovery of MB were also investigated. The mechanism of desorption of MB from the surface of starch was established by analyzing the weight loss profiles for different mixtures containing water, MB, WF or starch and yeast. Finally, the MB-WF and MB-starch species were fermented using diastase enzyme and yeast and the products formed were characterized by chemical, UV-visible spectroscopic and gas chromatographic analyses. The fermentation process was found to successfully convert starch to ethanol without decolorizing the MB species present in the residue. Dhaka Univ. J. Sci. 63(2):119-124, 2015 (July)